Do natural resources define convergence clubs? Empirical evidence from the Kazakh regions - Miriam Frey; Carmen Wieslhuber; Daniel Frey (Institut für Ost- und Südosteuropaforschung (IOS), 2013)
This paper deals with the hypothesis that natural resources are important in forming convergence clubs. We check this hypothesis by applying a dependence and an endowment measure of natural resource abundance and a regression tree analysis. The results indicate that for the Kazakh regions natural resources indeed play an important role in forming convergence clubs. It is further shown that rather natural resource endowment than resource dependence determines initial conditions and thereby convergence clubs.
urn:nbn:de:101:1-20130422836
Keywords: O13; O47; O53; 330; Convergence clubs; natural resources; regression tree; Kazakhstan